Effect of Cross Contamination on Berries of Solanum anguivi Lam and Change of Some Antinutrients of Their Berries During Post-Harvest Storage - Dan, C.G.; Dje, K.M.; Ban, L.K.; Nemlin, J.G.; Kouame, P.L. (Pakistan Journal of Nutrition, 2014)
The aim of this study was to evaluate the effect of cross-contamination on Solanum anguivi Lam berries and the assessment of some antinutritional compounds of berries as affected by ripening stage (green, yellow, orange and red) during the post-harvest storage. Indeed, the rates of ripening and alteration with and without cross-contamination were determinated during ripening. The antinutritional factors such as total oxalate, phytate, tannin and alpha-amylase inhibitor contents were also investigated. Furthermore, the results showed that the rates of ripening and alteration of berries without cross-contamination varied during post-harvest storage. Indeed, the rates of ripening and alteration S. anguivi Lam berries increased much more when there was a cross-contamination. All berries were altered at the ninth day of post-harvest storage with cross-contamination while they were all altered at fourteenth day without cross-contamination. As for the antinutritional factors, the ANOVA showed that the ripening stage had significant effect (p